Athletic training process quality rating by express tests of heart rate variability in view of individual type of regulation - Shlyk, N. I.; Lebedev, E. S.; Vershinina, O. S. (Theory and Practice of Physical Culture, 2019)
The study analyzes some aspects of the practical experience accumulated by a new experimental project to rate the training workloads versus the individual HR variations and autonomic regulation of heart rate, with elite cross-country skiers and biathletes from Udmurt Republican teams sampled for the study. The tests were dominated by daily express tests of the HR variations, with the test data and analyses used to design a new method to rate the exposure to overtraining risks and potential health disorders and prevent the training workloads coming in conflict with the cardiac performance control systems. A special priority in the HRV analyses was given to the individual autonomic regulation test data. The daily HRV express tests made it possible to map out the individual autonomic regulation features, and the body rehabilitation potentials to provide guiding frames for the individual training system design, management and competitive performance forecast purposes. The individual HRG profiles helped us detect serious irregularities in the skiers` and biathletes` training policies and practices. It was found, among other things, that the standard non-individualized training workloads insensitive to the autonomic regulation types expose the athletes to overtraining risks that are particularly high for the ones tested with low reserve capacities. It was further found that overtraining result in negative adjustments of the reactive mechanisms and stable pathologies in the cardiac performance control systems. The study also found that the training systems were customized neither to the individual autonomic regulation types nor to the altitude training cycles, and this negligence has often resulted in the autonomic regulation imbalances in early stages (first and the following micro-cycles) of the training process. Further trainings of the athletes with health disorders were found to mobilize the still untapped bodily resources with further aggravation of the autonomic regulation. Furthermore, in cases of transfers of athletes from one coaching team to another, the new coaches were found negligent of the prior training systems, experiences and workloads, and the revisions were tested to further aggravate the autonomic regulation, adaptability and resources in the precompetitive trainings at special detriment to the competitive performance. It was also found that excessive training workloads in combination with sauna may be detrimental to rehabilitation processes in the young athletes. The study data showed a close correlation between functionalities of the cardiac performance control systems and competitive success rates.